Genome Sequencing of 10 Helicobacter pylori Pediatric Strains from Patients with Nonulcer Dyspepsia and Peptic Ulcer Disease - Nunes, Alexandra (2015)
We present draft genome sequences of 10 Helicobacter pylori clinical strains isolated from children. This will be important for future studies of comparative genomics in order to better understand the virulence determinants underlying peptic ulcer disease.